Exploring nutritional and bioactive properties of Maranta arundinacea L.: An unconventional food plant - Oliveira, Yasmine Fernandes; Junior, Rodolfo Dantas Lima; Simão, Jorge Luiz Souza; Dias, Tiago; de Castro Ferreira, Tânia Aparecida Pinto; Cruz, Maurício Vicente; Fernandes, Kátia Flávia; Sperança, Marco Aurélio [UNESP]; Pereira, Fabiola Manhas Verbi [UNESP]; Pereira-Filho, Edenir Rodrigues; Costa, Larissa Silva; Lopes, Patricia Santos; et al. (Elsevier, 2025)
Unconventional Food Plants offer significant dietary and economic potential due to their rich nutritional and mineral content. Maranta arundinacea stands out for its food potential and use in the pharmaceutical field. This study aimed to analyse the nutritional, chemical and bioactive properties composition of the aerial and rhizomatic parts of M. arundinacea, highlighting their potential applications. The nutritional analysis revealed that protein and fibre content in the aerial parts (13.37 %) was significantly higher compared to the rhizomatic parts (5.12 %). Among the compounds identified through the Global Natural Product Social Molecular Networking (GNPS), rutin, quercetin, and kaempferol derivatives were the most prominent. These compounds are well known for their antioxidant properties, demonstrated against ABTS+, DPPH, and FRAP assays, which contribute to the overall health benefits of M. arundinacea. Collectively, these findings underscore the value of M. arundinacea as a valuable source of both nutritional and pharmacological benefits, supporting its long-term use as a valuable food, dietary supplement, and medicinal resource.